2021
DOI: 10.1186/s40249-021-00864-x
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographical characteristics of Schistosoma mansoni endemic areas in Ethiopia: a systematic review and meta analysis

Abstract: Background In Ethiopia, schistosomiasis is caused by Schistosoma mansoni and S. haematobium with the former being widespread and more than 4 million people are estimated to be infected by S. mansoni annually with 35 million at risk of infection. Although many school- and community-based epidemiological surveys were conducted over the past decades, the national distribution of schistosomiasis endemic areas and associated socio-environmental determinants remain less well understood. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…It is interesting to note that the model performance was also influenced by elevation, which is the most influential variable in the WC-based model and the second most in the SDSM-based model. This result confirmed that elevation was an important indicator for spatial monitoring of snail-borne diseases because certain ranges of elevation favor some snail species [ 15 ]. Consequently, elevation can be used to help identify the populations most vulnerable to schistosomiasis [ 55 ].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…It is interesting to note that the model performance was also influenced by elevation, which is the most influential variable in the WC-based model and the second most in the SDSM-based model. This result confirmed that elevation was an important indicator for spatial monitoring of snail-borne diseases because certain ranges of elevation favor some snail species [ 15 ]. Consequently, elevation can be used to help identify the populations most vulnerable to schistosomiasis [ 55 ].…”
Section: Discussionsupporting
confidence: 63%
“…For example, a study in the United States showed a potentially suitable habitat for three different fishes [ 53 ], and Dal Maso and Montecchio [ 54 ] studied the geographical distribution of ash dieback disease among trees in Europe. Results from our ensemble models showed that the majority of suitable areas for S. mansoni in Ethiopia were located in the West Montane and Rift Valley ecozones [ 15 ]. The findings largely agreed with reports of the high rate of infection in villages around Lake Tana and in rift valley areas near Lake Ziway and Lake Abaya reported three decades ago [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled prevalence of S. mansoni infection among children was highest in the SNNPR 41.49% (95%CI: 19.52-63.46) followed by the Amhara region 41.11%, (95%CI: 30.41-51.80), the Tigray region 31.4%, (95%CI: 11.72-51.09), and the Oromia regional state 28.98%, (95%CI: 18.85-39.10). This variation might be due to the different environmental and ecological variations, the difference in population density, and variability in efficacy of praziquantel [81][82][83]. The difference in environmental sanitation, personal hygiene, altitude differences, sanitation of streams/rivers, ponds, epidemiology of the snail vector, habit of open defecation, utilization of night soil as a fertilized might also contribute to the difference [84].…”
Section: Discussionmentioning
confidence: 99%
“…Schistosoma mansoni is the predominant cause of schistosomiasis in Ethiopia. Several studies were conducted on the prevalence of S. mansoni in different endemic areas of Ethiopia [20][21][22][23][24]. Understanding the impact of S. mansoni on the human coagulation system and platelet parameters are vital for planning, monitoring, and evaluating strategies to control schistosomiasis-associated morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%